Group Guidance Service Strategy Using Reframing Techniques to Increase Self-Confidence in Students Experiencing Bullying - Alyana, Adinda Ayu; Agus Basuki (LP3kM Buddhi Dharma University, 2026)
Bullying can undermine students’ self-confidence, weaken their psychological resilience, and limit their willingness to participate in academic and social activities at school. This study examined the effectiveness of group guidance services using reframing techniques to improve the self-confidence of students who had experienced bullying. A pre-experimental one-group pre-test–post-test design was employed. The participants were nine Grade XI students of SMA 1 Mejobo, selected purposively from 33 students based on low self-confidence scores and recommendations from the guidance and counseling teacher. The intervention consisted of group guidance sessions using reframing techniques, through which students were encouraged to reinterpret bullying experiences in a more adaptive, constructive, and self-empowering manner. Data were collected using a self-confidence scale and analyzed through descriptive statistics and the Wilcoxon signed-rank test. The results showed that the mean self-confidence score increased from 40.11 in the pre-test to 61.56 in the post-test, with a mean gain score of 21.44. The Wilcoxon analysis indicated a statistically significant difference between pre-test and post-test scores. These findings suggest that reframing techniques can be integrated into responsive guidance and counseling services to strengthen students’ self-confidence after bullying experiences, particularly within school-based preventive and curative counseling programs for adolescents.